Studying electromagnetic signal of rock effected by acoustic impact under uniaxial compression; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Bespalko (Bespal'ko) A. A. Anatoly Alekseevich; Yavorovich L. V. Ludmila Vasilievna; Pomishin E. K. Evgeny Karlovich; Fedotov P. I. Pavel Ivanovich (High energy processes and external exposure of materials, 2016)
Title screen